Progress and prospects in metabolic engineering approaches for isoprenoid biosynthesis in microalgae - Sonia Mohamadnia; Borja Valverde-Pérez; Omid Tavakoli; Irini Angelidaki (Biotechnology for Biofuels and Bioproducts)
Abstract Isoprenoids constitute a large and various number of bio-compounds, with many profitable applications in pharmaceutical, nutraceutical, and industrial fields. The complexity of isoprenoid molecules leads to a challenging, expensive, and environmentally unfriendly chemical synthesis of these metabolites. In addition, the awareness and desire of many consumers for products generated by natural microbial processes has increased recently. Metabolic engineering tools and synthetic biology strategies have been used as a means for the enhancement and optimization of the natural isoprenoid biosynthetic pathways of wild strains. Microalgae as production organisms have been manipulated for the bioproduction of diverse isoprenoids. Particularly when cultivated in unsuitable conditions (such as wastewater, unbalanced nutritional sources, and distinct environmental conditions), microalgae can adjust their metabolic pathways and generate compounds with significant technological potential. Several metabolic engineering approaches have been developed, modifying the metabolic pathways in microalgae to redirect the flow of carbon toward isoprenoid biosynthesis, including pathway engineering, strain improvement, and synthetic biology. In this review, some beneficial features of these high-value metabolites are summarized. Besides, recent advancements in metabolic engineering approaches for the biosynthesis of isoprenoids are discussed in detail. At last, the viewpoints and challenges for the biosynthesis of novel compositions with isoprene units in the microalgae are also included.